PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA PIAS-PIAS KATA DIGITAL PADA SISWA TUNAGRAHITA DI SDN JIWAN 02 MADIUN - Prastyo Budingsih; Mochamad Nursalim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the improvement of early reading skills in mentally retarded students in Inclusive Schools. Comparison of early reading skills in mentally retarded students in grade II in Inclusive Schools based on the results of the analysis between conditions before being given intervention, when being given intervention and after being given intervention. The data collection technique is a performance test. The subject in this study was one mentally retarded student in grade II in an inclusive school with the initials R. This study used an experimental method, namely using Single Subject Research (SSR) with an A-B-A design. The conclusion of this study is that students' early reading skills have increased, this is due to the influence of providing intervention through digital word stages.